Interannual Variations of Surface Currents and Transports in the Sicily Channel Derived From Coastal Altimetry. Issue 11 (2nd November 2017) - Jebri, Fatma; Zakardjian, Bruno; Birol, Florence; Bouffard, Jérôme; Jullion, Loïc; Sammari, Cherif
Abstract: A 20 year coastal altimetry data set (X‐TRACK) is used, for the first time, to gain insight into the long‐term interannual variations of the surface circulation in the Sicily Channel. First, a spectral along with a time/space diagram analysis are applied to the monthly means. They reveal a regionally coherent current patterns from track to track with a marked interannual variability that is unequally shared between the Atlantic Tunisian Current and Atlantic Ionian Stream inflows in the Sicily Channel and the Bifurcation Tyrrhenian Current outflow northeast of Sicily. Second, an empirical altimetry‐based transport‐like technique is proposed to quantify volume budgets inside the closed boxes formed by the crossing of the altimetry tracks and coastlines over the study area. A set of hydrographic measurements is used to validate the method. The inferred altimetry transports give a well‐balanced mean eastward Atlantic Waters baroclinic flow of 0.4 Sv and standard deviations of 0.2 Sv on a yearly basis throughout the Sicily Channel and toward the Ionian Sea, which is fairly coherent with those found in the literature. Furthermore, the analysis allows to quantify the intrusions of Atlantic Waters over the Tunisian Shelf (0.12 ± 0.1 Sv) and highlights two main modes of variability of the main surface waters path over the Sicily Channel through the Bifurcation Atlantic Tunisian Current and Atlantic Ionian Stream systems. Some physical mechanisms are finally discussed with regards to changes in the observed currents and transports. Key Points: A 20 year time series of coastal altimetry reveals interannual variability modes of the surface circulation in the Sicily Channel The variations of its volume transports are estimated with an empirical transport‐like model Interannual variability results from the Atlantic waters inflow and modulations of the mesoscale activity in coupled or compensating ways